MASALAH YANG DIHADAPI PESERTA DIDIK TINGGAL KELAS DI SEKOLAH DASAR NEGERI 05 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Ivhone, Bertha; Helma, Helma; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
This research was motivated the students repetition such as; the students often absen, and there are some students still can not read. This study is a qualitative. Informants in this study is the students repetiton as much as 3 core informants, and 9 additional informants in SDN 05 Lembah Melintang West Pasaman. Data were collected through observation and interviews. The accuracy of the data was tested by using triangulation of data, from the data were analyzed with an interactive model that consists of data collection, data reduction, presentation and conclusion. The results of the study show that ( 1 ) The studentsâ repetition problem come fromÂ internal factors, the students feel ashamed and inferior to their friends, so the students be more silent when teaching learning process. ( 2 ) The studentsâ repetition problem from external factors is the learners will be ostracized by their friends. Considering of this research the researcher recomended to the learners have to attention their teacher while teaching learning process, repeat the lessons that have been learned, and the teacher should give more attention to the students repetition. Moreover the head master expected to support the implementation of the learning that has been prepared by the teacher. Also expected to the parents to give attention to the students.